WEBSITE INTERFACE EVALUATION USING GOAL-DIRECTED DESIGN METHOD IN XYZ UNIVERSITY - Abyakta, Irfan Jesia; Perdanakusuma, Andi Reza; Pramono, Djoko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2023)
Abstract: This research focuses on designing an interface refinement for the XYZ University company profile website that facilitates public information services. This research aims to increase the website's usability value by implementing the Goal-Directed Design (GDD) method in website interface refinement. GDD provides solutions that meet user needs and goals and address business goals. This research begins the interface design process by identifying user behavior patterns and goals to help deepen understanding of the domain, business goals, and technical constraints that will be used as a reference in website interface design refinement. Furthermore, usability testing is conducted using the System Usability Scale (SUS) as the measurement parameter. The usability aspects assessed in this research are effectiveness, efficiency, and satisfaction. Usability testing is conducted on the current website interface design and the website interface refinement design. Tests were conducted on six participants, consisting of three XYZ University students and three members of the general public. The findings show that the website's usability has increased from the previous value of 49.16 to 83.33. Based on the SUS score interpretation, the value that was previously categorized as